2012
DOI: 10.1364/ol.37.001685
|View full text |Cite
|
Sign up to set email alerts
|

Ultrabroadband supercontinuum generation in a CMOS-compatible platform

Abstract: We demonstrate supercontinuum generation spanning 1.6 octaves in silicon nitride waveguides. Using a 4.3 cm-long waveguide, with an effective nonlinearity of γ=1.2 W(-1) m(-1), we generate a spectrum extending from 665 nm to 2025 nm (at -30 dB) with 160 pJ pulses. Our results offer potential for a robust, integrated, and low-cost supercontinuum source for applications including frequency metrology, optical coherence tomography, confocal microscopy, and optical communications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
120
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 204 publications
(125 citation statements)
references
References 23 publications
(26 reference statements)
0
120
1
Order By: Relevance
“…Hydex and SiN offer the advantage of much lower linear and nonlinear losses as well as transparency well into the visible. It is interesting to compare the broadband frequency combs with SCG in Hydex waveguides [92] where a spectral width > 350 nm was achieved (limited by experimental measurement capability), as well as with SCG in 1100-nm wide SiN nanowires [93]. When pumping at 1335 nm in this platform SCG resulted in a spectrum spanning 1.6 octaves, from 665 nm to 2025 nm.…”
Section: Supercontinuum Generationmentioning
confidence: 99%
See 1 more Smart Citation
“…Hydex and SiN offer the advantage of much lower linear and nonlinear losses as well as transparency well into the visible. It is interesting to compare the broadband frequency combs with SCG in Hydex waveguides [92] where a spectral width > 350 nm was achieved (limited by experimental measurement capability), as well as with SCG in 1100-nm wide SiN nanowires [93]. When pumping at 1335 nm in this platform SCG resulted in a spectrum spanning 1.6 octaves, from 665 nm to 2025 nm.…”
Section: Supercontinuum Generationmentioning
confidence: 99%
“…Remarkably, both of these results were enabled by a high effective nonlinearity, negligible TPA and most significantly, by very flexible dispersion engineering. SCG is significantly enhanced if the pulse is launched near a zero groupvelocity dispersion (GVD) point or in the anomalous GVD regime [93][94][95][96]. The former minimizes temporal pulse broadening, thereby preserving high peak powers and thus maintaining a strong nonlinear interaction.…”
Section: Supercontinuum Generationmentioning
confidence: 99%
“…A large shock time enables the observation of soliton self-frequency shift in silicabased fibers with short lengths (O(10) cm) and intense pump powers (O(1) kW) [39], while in SiN-based waveguides (not resonators), the Raman effect is not observed [40,41]. However, in microresonators, due to the cavity building (finesse F = D1 κ ≈ O(100 − 1000)), the lightmaterial interaction length is effectively increased (to O(1) m) and meanwhile the pulse peak power is dramatically promoted (e.g.…”
Section: (E)mentioning
confidence: 99%
“…In a variety of waveguides, including silicon nitride waveguides [24] and chalcogenide waveguides [25] supercontinuum generation has been demonstrated. It can be shown that the widest supercontinuum spectra are generated when nonlinear waveguides are pumped at a wavelength were they have a small anomalous dispersion (for positive n 2 ) [20].…”
Section: Ultrashort Pulses In the Telecommunication Bandmentioning
confidence: 99%
“…A multitude of linear and nonlinear functions in silicon nitride [14] have been demonstrated. However, most of these, such as supercontinuum generation [24] and comb generation [29,31], have focused on the telecom wavelength band. In addition to this work, a broadband source covering red to near-infrared wavelengths is interesting for biophotonics applications.…”
Section: Sin Waveguide Structures For Nonlinear Optics In the Visiblementioning
confidence: 99%